Chemical functionality of multidomain peptide hydrogels governs early host immune response. (February 2020) - Lopez-Silva, Tania L.; Leach, David G.; Azares, Alon; Li, I-Che; Woodside, Darren G.; Hartgerink, Jeffrey D.
Abstract: Multidomain Peptide (MDP) hydrogels are nanofibrous materials with many potential biomedical applications. The peptide sequence design of these materials offers high versatility and allows for the incorporation of various chemical functionalities into the nanofibrous scaffold. It is known that host response to biomaterials is strongly affected by factors such as size, shape, stiffness, and chemistry. However, there is a lack of fundamental understanding of the host response to different MDP hydrogels. In particular, it is unknown what effect the chemical functionality displayed on the nanofiber has on biological activity. Here we evaluated the early inflammatory host response to four MDP hydrogels displaying amines, guanidinium ions, and carboxylates in a subcutaneous injection model. While all the studied peptide materials possess similar nanostructure and physical properties, they trigger markedly different inflammatory responses. These were characterized by immunophenotyping of the cellular infiltrate using multi-color flow cytometry. The negatively-charged peptides elicit minimal inflammation characterized by tissue-resident macrophage infiltration, fast remodeling, and no collagen deposition or blood vessel formation within the implants. In contrast, the positively-charged peptides are highly infiltrated by immune cells, are remodeled at a slower rate, promote angiogenesis, and result in a high degree of collagen deposition. The presence of dynamic cell phenotypes characterizes the inflammation caused by the lysine-based peptide, including inflammatory monocytes, macrophages, and lymphoid cells, which is seen to be resolving over time. The arginine-based hydrogel shows higher inflammatory response with a persistent and significant infiltration of polymorphonuclear myeloid-derived cells, even ten days after implantation. This understanding of the immune response to peptide biomaterials improves our ability to design effective materials and to tailor their use for specific biomedical applications. Graphical abstract: Image 1